Optimization and Comparison of Linear and Curved Cone Contraction Designs Using the CFD Method for the Development of a Two-Dimensional Low-Subsonic Wind Tunnel - Sulthan Dzaki Ahmada; Hendrix Noviyanto Firmansyah; Samsudin Anis (Jurnal Inovasi Mesin, 2026)
The geometry design of the contraction cone plays an important role in determining the flow performance in a subsonic wind tunnel. This study aims to examine and compare two forms of contraction cone design, namely the linear model and the polynomial curve, in the development of a two-dimensional Low Subsonic Wind tunnel using the Computational Fluid Dynamics (CFD) numerical simulation method. The main objective of this study is to evaluate the effect of geometric shapes on velocity distribution, flow uniformity, and aerodynamic performance in the test chamber. Simulations were carried out using ANSYS Fluent software with the k-ω SST turbulence model, and the NACA 4412 airfoil was used as a test object to observe the aerodynamic forces. The simulation results show that the contraction cone with the polynomial curve design produces a more uniform flow, higher speed, and a better lift coefficient (Cl) than the linear design. In addition, the curve design is also able to suppress flow disturbances such as flow separation and boundary layer effects. Based on these findings, the contraction cone with a polynomial curve profile is more recommended for application in a two-dimensional subsonic wind tunnel to improve the efficiency and accuracy of aerodynamic testing.